Proceedings of the 19th International Conference on Enterprise Information Systems 2017
DOI: 10.5220/0006387803850392
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for Value-driven Semantic Data Quality Management

Abstract: Abstract:This paper reflects on six years developing semantic data quality tools and curation systems for both largescale social sciences data collection and a major web of data hub. This experience has led the author to believe in using organisational value as a mechanism for automation of data quality management to deal with Big Data volumes and variety. However there are many challenges in developing these automated systems and this discussion paper sets out a set of challenges with respect to the current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The authors Stohr and Zhao, (2001) ;Isaksson, (2006) and Kubiak and Benbow, (2009) defined a business process as a series of interrelated steps consisting of required resources and activities that convert inputs into outputs to serve a meaningful purpose within an organization. Each step in the process consists of transforming some previous state and/or condition (input) into a new state and/or condition (output) until the final product or service is reached or producing a given result (Davenport, 1993;Brennan, 2017). Lindsay et al, (2003) and Lee et al, (2007) referred to a business process as a relationship between clearly identified inputs and outputs, where inputs are transformed into outputs using a set of activities which add value to the inputs.…”
Section: 2business Process -Transformation Of Input Into Outputmentioning
confidence: 99%
“…The authors Stohr and Zhao, (2001) ;Isaksson, (2006) and Kubiak and Benbow, (2009) defined a business process as a series of interrelated steps consisting of required resources and activities that convert inputs into outputs to serve a meaningful purpose within an organization. Each step in the process consists of transforming some previous state and/or condition (input) into a new state and/or condition (output) until the final product or service is reached or producing a given result (Davenport, 1993;Brennan, 2017). Lindsay et al, (2003) and Lee et al, (2007) referred to a business process as a relationship between clearly identified inputs and outputs, where inputs are transformed into outputs using a set of activities which add value to the inputs.…”
Section: 2business Process -Transformation Of Input Into Outputmentioning
confidence: 99%